ANALISIS HUKUM KETENAGAKERJAAN TERHADAP PERMINTAAN BENEFIT THR OLEH MITRA PLATFORM TRANSPORTASI DALAM JARINGAN (ONLINE) - Parlin Bachtiar Sinaga (LEX LAGUENS: Jurnal Kajian Hukum dan Keadilan, 2025)
The existence of digital transportation platforms has been increasingly felt by the Indonesian public in recent years. This not only helps users, who are facilitated by online bookings, but also drivers, better known as online motorcycle taxis. More than a million drivers currently rely on online transportation for their livelihoods. This job is considered relatively easy to "apply for." Furthermore, the work mechanism is carried out through a partnership scheme, not an employee-employer relationship. As a result, there is a legal vacuum where there is no equal protection regulated by the Labor Law for online transportation partners (drivers). The tip of the iceberg occurred during the run-up to Eid al-Fitr 2025, when a number of online motorcycle taxi drivers demanded THR (Holiday Allowance) benefits, like workers in general. This article attempts to analyze the legal aspects that arise from this. The research method used in this research is normative legal research (legal research) which is usually "only" a document study, which uses legal material sources in the form of laws and regulations and other provisions, legal theories, and opinions of scholars. It is hoped that in the future the analysis in this paper can be useful for stakeholders for justice and legal certainty.